Novel neck cold compress bag - SHI ZHONGNA; GAO QIN; XU WENHUA (2012)
The invention provides a novel neck cold compress bag, which comprises a left ice bag region and a right ice bag region, wherein one end of each ice bag region is connected with a head region; one end of the head region is provided with a head snap fastener; the other end of each ice bag region is connected with a lower jaw cloth bag region; one end of the lower jaw cloth bag region is provided with a lower jaw region snap fastener; a head fixing band snap fastener is arranged correspondingly to each head snap fastener; a head fixing band is arranged between the two head fixing band snap fasteners; an included angle alpha between both sides of the lower jaw cloth bag region is 55-65 degrees; in the head region, an angle beta1 is 115-125 degrees, an angle beta2 is 45-55 degrees, and an angle gamma is 95-105 degrees; and the head fixing band is opened in the middle. The neck cold compress bag disclosed by the invention is designed according to the physiological positions of a head and a neck; looseness can be a